2010
DOI: 10.3141/2143-19
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Carsharing on Household Vehicle Holdings

Abstract: Carsharing has grown considerably in North America during the past decade and has flourished in metropolitan regions across the United States and Canada. The new transportation landscape offers urban residents an alternative to automobility, one without car ownership. As car-sharing has expanded, there has been a growing demand to understand its environmental effects. This paper presents the results of a North American carsharing member survey (N = 6,281). A before-and-after analytical design is established wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
139
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 419 publications
(146 citation statements)
references
References 8 publications
4
139
1
2
Order By: Relevance
“…12 Recent evidence for the USA has shown that 11 Car sharing reduced car ownership levels in a US sample by half [87]. 12 We are aware that there are opposite views about this, for example Cox [96,97].…”
Section: Threatsmentioning
confidence: 99%
“…12 Recent evidence for the USA has shown that 11 Car sharing reduced car ownership levels in a US sample by half [87]. 12 We are aware that there are opposite views about this, for example Cox [96,97].…”
Section: Threatsmentioning
confidence: 99%
“…As of January 2014, there were approximately 1.23 million car-sharing members (traditional and one-way) with access to over 17,000 vehicles in the USA (Le Vine et al 2014;Susan Shaheen and Cohen 2013;Susan Shaheen and Cohen 2014). Based on surveys in 2005 and 2008, research in the USA has found that overall traditional car sharing reduces or delays car ownership, removes 9-13 cars from the road with each car-sharing vehicle, increases fuel economy of vehicles driven, reduces greenhouse gas emissions, reduces vehicle miles traveled (VMT), and reduces public transit use while increasing walking, biking, and carpooling (Cervero et al 2007;Martin et al 2010;Martin and Shaheen 2011a;Martin and Shaheen 2011b, c). The number of cars removed from the road may be lower when looking at a larger share of the population and taking into consideration self-selection bias in the analysis (Clewlow 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The car-sharing space Car sharing is a relatively new mobility option, which began to gain popularity in the early 2000s in North America (E. Martin et al 2010) and slightly earlier in Europe (Jorge and Correia 2013). There are several different models of car sharing available today: Btraditional^or A-to-A; Bone-way,^Bfree-floating,^or A-to-B; and peerto-peer or personal vehicle sharing (note on-demand services or transportation network companies (TNCs), such as Uber, are not considered car sharing in the literature).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Most notable is, that it is convenient and cost effective for users [7], [8], and additionally, by being a flexible (short-term) transportation service, it can complement classical means of transportation by intertwining individual mobility with existing public transportation options [9], [10]. Furthermore, earlier studies have exhibited that compared to trips with a privately owned car, car sharing has the capability to decrease the individual car-bound mobility by up to 30% [2], [11]. Beyond the reduced car-bound mobility and the derived lower emissions, using car sharing results in a reduced parking demand and less noise, which makes it an environmentally sustainable form of transportation, for urban areas [2], [11].…”
Section: Introductionmentioning
confidence: 99%